Tinea Korporis Et Cruris - Yaiza Aynaya Mailyn; Mohammad Mimbar Topik (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Dermatophytes are a group of fungi that have the ability to attach to keratin and use it as a source of nutrition which allows the fungus to colonize tissues that contain keratin, such as the stratum corneum of the epidermis, hair and nails. This disease can attack all ages (1). Tinea corporis and cruris are dermatophytes that infect the skin and are caused by Trichophyton sp, Microsporum sp, and Epidermophyton sp. Dermatophytes infecting skin containing keratin are classified based on body location, such as tinea corporis (skin other than hairy areas, body, hands, or feet) and tinea cruris (groin & perineal area) (2).